Sustainability of arsenic mitigation interventions—an evaluation of different alternative safe drinking water options provided in Matlab, an arsenic hot spot in Bangladesh - Hossain, Mohammed; Rahman, Shamsun N.; Bhattacharya, Prosun; Jacks, Gunnar; Saha, Ratnajit; Rahman, Marina (Frontiers in Environmental Science, 2015)
The wide spread occurrence of geogenic arsenic (As) in Bangladesh groundwater drastically reduced the safe water access across the country. Since its discovery in 1993, different mitigation options tested at household and community scale have resulted in limited success. In an arsenic hotspot of southeastern Bangladesh, 841 arsenic removal filter (ARF), 190 surface water filter membrane, 23 pond sand filter (PSF), 147 rain water harvester (RWH) and 59 As-safe tubewell were distributed among the severely exposed population by AsMat, a Sida supported project. After three-four years of providing these safe water options, this study was carried out during 2010-2011 for performance analysis of these options, in terms of technical viability and effectiveness and thus to evaluate the preference of different options to the end users. Household and community based surveys were done to make an assessment of the current water use pattern as impact of the distributed options, overall condition of the options provided and to identify the reasons why these options are in use and/or abandoned. In total, 284 households were surveyed and information was collected for 23 PSF, 147 RWH and 59 tubewells. None of the filters was found in use. Among other options distributed, 13% of PSF, 40% RWH and 93% of tubewell were found functioning. In all cases, tubewells were found As-safe. About 89% of households are currently using tubewell water which was 58% before. Filter was abandoned for high cost and complicated maintenance. The use of RWH and PSF was not found user friendly and ensuring year round water quality is a big challenge. Arsenic-safe tubewell was found as a widely accepted option mainly because of its easy operation and availability of water, good water quality and negligible maintenance. This study validated tubewell as the most feasible option and holds significance for planning water supply projects, improving mitigation policy as well as developing awareness among users.